Systematic literature review on election and stock performance - Choo, Qin Jinga; Chia, Ricky Chee Jiun (Penerbit UMS, 2023)
Political factor is one of the main factors that influence investors’ decision-making. Considering that, this study presents a systematic review of the research work, published on the topic of election effects and stock market behaviour. Through Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this study critically assessed and examined sixteen research studies, published between 1995 and 2021, in different regions across the globe. Based on the outcomes, most of these past studies highlighted that the election effects rely entirely on the political climate. If the election outcome benefits the economy, stock markets react positively. Moreover, stock market volatility was noted to be significantly impacted by elections. Higher volatility induced by election whenever there is unforeseen outcome and volatility adjusted back to normal when uncertainty resolve. The findings of this review are expected to reveal the knowledge of theoretical and literature significance on stock market behaviour around elections to researches and investor community. Finally, this paper reveals some significant research gap to advance the research agenda for future research.